Pemenuhan Hak Pendidikan Anak Berkebutuhan Khusus di SD Negeri 30 Palembang - Damayanti, Novi (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to describe the fulfillment of the rights to education for children with special needs (ABK) at the SD Negeri 30 Palembang. Type of qualitative descriptive research. Data collection techniques use questionnaires, interviews and observation methods. The research subjects were teachers and principals. The research results show that the school has been able to implement the inclusive school concept quite well. In general, the rights to education for ABK have been fulfilled amidst facilities and infrastructure that are not yet inclusive. This study provides a real picture of how inclusive education is implemented in elementary schools in Indonesia, especially in Palembang City. This case study can be used as an example for other schools trying to fulfill ABK's educational rights. It is hoped that the results of this research can contribute to the development of inclusive education policies at the local and national level. Apart from that, this research can also provide input for teachers, schools and other stakeholders in improving the quality of education for ABK.